Does Guidewire Exchange Influence Infection Rate Related to Catheters Used for Vascular Access in Children on Chronic Hemodialysis?. Issue 1 (27th October 2016) - Rus, Rina R; Battelino, Nina; Ponikvar, Rafael; Premru, Vladimir; Novljan, Gregor
Abstract: A central venous catheter (CVC) can either be inserted "de novo" or placed by guidewire exchange (GWE). From September 1998 to September 2015, 32 children (19 boys, 13 girls) were hemodialyzed in our unit by using a CVC. The mean age at CVC insertion was 12.6 ± 0.5 years. A total of 121 uncuffed catheters were placed, either "de novo" or by GWE in 64 (52.9%) and 57 (47.1%) cases, respectively. The most frequent cause for line revision was catheter dysfunction in 40/121 (33.1%) patients. The overall incidence of bacteremia was 1.5/1000 catheter‐days. The incidence in newly inserted and GWE catheters was 1.4 and 1.7/1000 catheter‐days, respectively. The difference did not reach statistical significance ( P =  0.939). The infection rate correlated with patient age, and was higher in younger children ( P =  0.006). GWE is an effective option of line revision, and did not influence the infection rate in our study.